2017
DOI: 10.3390/w9070454
|View full text |Cite
|
Sign up to set email alerts
|

Treated Greywater Reuse for Hydroponic Lettuce Production in a Green Wall System: Quantitative Health Risk Assessment

Abstract: Abstract:The scarcity and pollution of freshwater are extremely crucial issues today, and the expansion of water reuse has been considered as an option to reduce its impact. This study aims to assess the efficiency of an integrated greywater treatment system and hydroponic lettuce production as a part of a green wall structure, and to evaluate the health risk associated with the production and consumption of lettuce through a quantitative microbial risk assessment (QMRA) and a chemical health risk assessment. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 37 publications
3
21
0
Order By: Relevance
“…Therefore we suggest that digested brewery wastewater has the potential to provide plants with the required nutrients to obtain high yields, at least with certain crops. This is consistent with a similar study that grew tomato, Solanum lycopersicum, using digested brewery wastewater [12] and other research that successfully used nutrient solutions partially or totally made with wastewater or organic waste for soilless production [10,[39][40][41][42].…”
Section: Discussionsupporting
confidence: 91%
“…Therefore we suggest that digested brewery wastewater has the potential to provide plants with the required nutrients to obtain high yields, at least with certain crops. This is consistent with a similar study that grew tomato, Solanum lycopersicum, using digested brewery wastewater [12] and other research that successfully used nutrient solutions partially or totally made with wastewater or organic waste for soilless production [10,[39][40][41][42].…”
Section: Discussionsupporting
confidence: 91%
“…The concentration of arsenic in lettuce from Source Waters 2, 3 and 4, however, were above the maximum allowable level. A study by Eregno et al [12] involved growing lettuce hydroponically with treated greywater with added human urine and found that lettuce leaves across all treatments were below estimated Health Risk Index and Target Hazard Quotient values and therefore implied to have low health risk for consumption. However, Eregno et al [12] did report that the HRI for As and THQ for As and Cr were relatively higher than the other metal(loid)s tested, which is similar to our findings for arsenic.…”
Section: Resultsmentioning
confidence: 99%
“…Treatment of wastewater has been shown to be possible over 7 days with a Pistia stratiotes phytofiltration lagoon, with an average biomass production of 5.8 g of dry weight per square meter per day [11]. Lettuce (Lactuca sativa) can successfully be produced with treated greywater without posing a substantial health risk for pathogens or metal(loid)s, while also providing a 5.1 log10 reduction of E. coli in the final effluent [12]. Hydroponic barley (Hordeum vulgare) production using wastewater has been investigated [13] and found a decrease in yields of 47% and 17% for conventional activated sludge and lagoon system water compared to half-strength Hoagland Solution, concluding that further fertilization with wastewater would be necessary and that metal(loid) concentrations in plant tissue increased, but did not exceed, toxic levels.…”
Section: Introductionmentioning
confidence: 99%
“…In order to counteract this, disequilibrium atmospheric CO 2 dissolves in water through the liquid-air interface until equilibrium is reached, Eq. (7). Carbonic acid, Eq.…”
Section: Lime Chemical Precipitation (Lcp)mentioning
confidence: 99%